El transporte marítimo en el siglo XXI. Retos para la seguridad marítima y la protección medioambiental - Piniella Corbacho, Francisco (Gestión Portuaria y Logística, 2009)

Réflexion autour des dictionnaires de droit civil - Devinat, Mathieu (Jurilinguistique : entre langues et droits, 2005)
Par leur mode de rédaction, les dictionnaires de droit civil révèlent une conception du sens en droit qui se caractérise par son objectivité, son historicité et son unité, c’est-à-dire par un ensemble de qualités qui sont intimement liées dans l’imaginaire des civilistes. Ce faisant, les dictionnaires de droit civil présentent un certain découpage du monde qui ne tient pas toujours compte des sens multiples que les juristes attribuent aux termes fondamentaux de leur vocabulaire. C’est en dégageant l’origine et la raison d’être du décalage entre le sens tel qu’il est défini et celui qui est vécu que l’auteur montre à quel point les dictionnaires de droit civil s’inscrivent dans une relation complexe qu’entretiennent les juristes avec leur langage.
Keywords: Bilingual Legal Dictionaries; Dictionnaires juridiques bilingues; Droit Civil; Lexicographie; Lexicography

Qui contrôle l’arbitrage ? : autonomie des parties, pouvoirs des arbitres et principe d’efficacité - Kaufmann-Kohler, Gabrielle (Liber amicorum Claude Reymond : autour de l'arbitrage, 2004)

Droit des signes distinctifs: marques, nom commercial - Cruquenaire, Alexandre (Droit de l'informatique et des technologies de l'information : chronique de jurisprudence : 1995-2001, 2003)
Keywords: case law; cybersquatting; domain names; out-of-court settlement; trade name; trademark law; udrp

Rethinking consumer protection policy - Trebilcock, Michael (International Perspectives on Consumers' Access to Justice, 2003)
This is the version of record of an article authored by Michael Trebilcock and published by the Cambridge University Press.

International Trade & International Labour Standards - Trebilcock, Michael (International Economic Governance and Non-Economic Concerns, 2002)
This is an accepted manuscript of an article authored by Michael Trebilcock, and later published in International Economic Governance and Non-Economic Concerns.
Accepted: 2023-08-02T19:59:53Z
Keywords: International Labour Standards; International Trade; Labour law; NAFTA; Unfair competition; WTO

International trade policy and domestic food safety regulation: The case for substantial deference by the WTO Dispute Settlement Body under the SPS Agreement - Trebilcock, Michael; Soloway, Julie (The Political Economy of International Trade Law: Essays in Honor of Robert E. Hudec, 2002)
There has been a dramatic shift in the focus of trade policy concerns in recent years from the barriers that lie at the border to the barriers which exist “within the border.” The General Agreement on Tariffs and Trade/World Trade Organization (GATT/WTO) and other regional trading arrangements have been largely successful in reducing both the levels of tariffs worldwide and the scale of other border measures such as quotas. This has revealed a new and more subtle category of measures which restrict trade – the numerous regulations which governments enact to protect the health and safety of their citizens and the environment in which they live. Such regulations vary tremendously across borders: one nation's bunch of grapes is another nation's repository of carcinogenic pesticide residue. These efforts to protect citizens from the hazards of everyday life have become a virtual minefield for trade policy makers, in part because such differences can often be manipulated or exploited to protect domestic industry from international competition, and in part because even when there is no protectionist intent on the part of lawmakers, through a lack of coordination, mere differences in regulatory or standard-setting regimes can function to impede trade through increasing multiple compliance costs. It has thus become increasingly difficult to delineate the boundaries between a nation's sovereign right to regulate and its obligation to the international trading community not to restrict trade.
Accepted: 2023-08-02T20:19:47Z
Keywords: GATT; International Trade; Trade Policy; WTO

Attention ! Une spécialité peut en cacher une autre - Greenstein, Rosalind (Droit et langues étrangères 2 : Traductions juridiques, domaine du juriste, du linguiste ou du jurilinguiste ?, 2001)
Code: Droit et langues étrangères 2 : Traductions juridiques, domaine du juriste, du linguiste ou du jurilinguiste ?

Introduction - Benjamin-Labarthe, Elyette (Droit et langues étrangères : Concepts, problèmes d'application, perspectives, 2000)